Continuous ambient vibration monitoring of the arch dam of Mauvoisin. - Darbre, Georges R.
This paper presents the experimental programme and results of a continuous ambient vibrations recording programme carried out on the 250 m arch dam of Mauvoism. This project follows a series of previous measurements completed for seven different water levels. An automated system was set up on the dam and the ambient vibrations were recorded twice daily for a period of 6 months. Frequency shifts were tracked throughout the testing period and the effects of the varying water level were identified. The results confirmed the behaviour observed in previous ambient and forced vibration tests. The added mass effects are overcome by the stiffening of the dam due to increasing hydrostatic pressure for lower reservoir levels. This trend is then reversed for higher water levels. Any temperature related effects were not identified. The experimental techniques are briefly described and the frequency identification process and its limitations are discussed.
Keywords: Concrete dams; Ambient vibrations; Dynamic testing; Resonance frequencies; Reservoir level; Stiffness